Aplicación de los principios cooperativos para estructurar el balance social en la cooperativa de ahorro y crédito “La Libertad 3”, ubicada en la parroquia Pastocalle, cantón Latacunga, provincia Cotopaxi en el período 2014 - Cobos Escudero, Mónica Elizabeth (2015)
Nowdays, Popular and Solidarity Economy Law has a great importance for many cooperatives because they are agreed that the social balance will help inside and outside in order to ensure the right accomplishment. This research is based on seven macro dimensions application. They are supported by social balance model at “La Libertad 3” Cooperativa de Ahorro Y Crédito, during the 2014. This is taken as an a priori model of their relationship with internal customers, organizational environment, gender equality, equity cognitive, social and cultural respect, values, participation in solidarity economy, source and training method. Also, it helps to visualize the feasibility regard to continuously improve internal relationships which affect the working environment and services. They can strengthen the institution, in a competitive market within the cornerstones of cooperative management. Besides….